Reactions on catalytic probe surface during oxygen plasma treatment of polyether sulphone - Mozetič, Miran (Informacije MIDEM, 1998)
Experiments on the behavior of a nickel catalytic probe during activation of the surface of polyether sulphone in oxygen plasma are described. The temperature of the probe mounted 30 cm apart from inductively coupled RF oxygen plasma was measured for the case of empty dischaarge vessel and the case a sample with the dimensions of 8 cm x 1.2 cm x 0.4 cm was mounted in the middle of the discharge coil. It was found that both the maximum temperature and the first time derivative of the probe was much higher in the case of loaded discharge vessel than in the case of empty vessel. Both effects were described in terms of a higher probability for recombination of radicals such as CO on the probe surface than the recombination of neutral oxygen atoms.
Keywords: katalizatorji; kemijska kinetika; kisik; nikelj; plazma; polieter sulfon